Economic sustainability of water supply public policy in Brazil semiarid regions (Research, Society and Development, 2020)
Droughts affect semiarid regions worldwide, threatening economic activities and lives of people living in these places. In Brazil, 11% of the population inhabits the semiarid, and despite several mitigation measures taken by the State, it is still ranked as the most vulnerable Brazilian region and potentially the most affected by climate change. Throughout Brazilian history several public policies focused on water supply in the semiarid region have failed for different reasons. Two recurring arguments are the lack of financial resources and poor management. This work presents an analysis of a public policy that aims to provide quality and perennial water by desalting local brackish groundwater, the Programa Água Doce (PAD). We used the ecodevelopment theory to discuss the economic sustainability of the policy. The methodology used was a documental analysis, and a literature review to understand PAD’s main strengths and weaknesses. We found that the continuous flow of public and private investment was a decisive element to the implementation of the technology during the initial transference of responsibilities moment. In addition, by the gradual reduction of public investment, the management of the systems became local and funded by private resources from the beneficiaries. The PAD presents, in its dynamics, advances in the field of the dissemination of water treatment technologies and social technologies, especially in relation to the Management Agreements. However, the lack of processes for community empowerment and no strengthening of cooperativism resulted in disconnected systems that were not able to ensure economic sustainability.